Excellent, Lightweight and Flexible Electromagnetic Interference Shielding Nanocomposites Based on Polypropylene with MnFe2O4 Spinel Ferrite Nanoparticles and Reduced Graphene Oxide - Yadav, Raghvendra Singh; Anju; Jamatia, Thaiskang; Kuřitka, Ivo; Vilčáková, Jarmila; Škoda, David; Urbánek, Pavel; Machovský, Michal; Masař, Milan; Urbánek, Michal; Kalina, Lukas; Havlica, Jaromir (Nanomaterials (Basel, Switzerland), 2020)
In this work, various tunable sized spinel ferrite MnFe2O4 nanoparticles (namely MF20, MF40, MF60 and MF80) with reduced graphene oxide (RGO) were embedded in a polypropylene (PP) matrix. The particle size and structural feature of magnetic filler MnFe2O4 nanoparticles were controlled by sonochemical synthesis time 20 min, 40 min, 60 min and 80 min. As a result, the electromagnetic interference shielding characteristics of developed nanocomposites MF20-RGO-PP, MF40-RGO-PP, MF60-RGO-PP and MF80-RGO-PP were also controlled by tuning of magnetic/dielectric loss. The maximum value of total shielding effectiveness (SET) was 71.3 dB for the MF80-RGO-PP nanocomposite sample with a thickness of 0.5 mm in the frequency range (8.2-12.4 GHz). This lightweight, flexible and thin nanocomposite sheet based on the appropriate size of MnFe2O4 nanoparticles with reduced graphene oxide demonstrates a high-performance advanced nanocomposite for cutting-edge electromagnetic interference shielding application.
Keywords: magnetic loss; dielectric loss; spinel ferrite; electromagnetic interference shielding; nanocomposites